2013
DOI: 10.1177/0973801012466100
|View full text |Cite
|
Sign up to set email alerts
|

The Synchronisation of ASEAN-5 Stock Markets with the Growth Rate Cycles of Selected Emerging and Developed Economies

Abstract: One of the more significant findings from this study is that ASEAN-5 stock markets do not react as a whole to external shock from these four trading partners. Each stock market in ASEAN-5 responded differently in terms of direction and degree towards the influences of the economic condition in these emerging and developed economies. The ASEAN-5 stock markets were less correlated with economic activities in emerging economies but were more aligned with economic activities in developed economies. In summary, ASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The existing empirical analyses on the fluctuation in Indian economic activities and its impact on the stock markets in the Asian countries are still limited. Teng, Yen and Chua (2013b) found that Indian economic growth rate cycle was marginally concordant with stock markets' cycles. This finding did not literally prove whether the movement is just a coincident or a contagion effect.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The existing empirical analyses on the fluctuation in Indian economic activities and its impact on the stock markets in the Asian countries are still limited. Teng, Yen and Chua (2013b) found that Indian economic growth rate cycle was marginally concordant with stock markets' cycles. This finding did not literally prove whether the movement is just a coincident or a contagion effect.…”
Section: Literature Reviewmentioning
confidence: 95%
“…[8] Teng Kee Tuan et al studied the linkage of the stock markets between China and ASEAN through the synergy index, found that the stock market linkage of China and ASEAN has been growing since the establishment of the ASEAN Free Trade Area. [9][8] HH Lean and R Smyth studied the cointegration relationship of stock market between China and ASEAN, found that the impact was rapid in a short time and there was a cointegration relationship for a long time. [10] Lei C et al analysed the dynamic correlation coefficient between China and the ASEAN-5, and found that there was a cointegration relationship from 1994 and 2002.…”
Section: The Co-movement Between China and Asean Stock Marketsmentioning
confidence: 99%
“…The Malaysian stock market, in fact, was more resilient to changes in the Chinese stock market than the US stock market. In addition, Teng et al (2013) found that the ASEAN-5 stock market was closely integrated with the US and Japanese stock markets in terms of finance, by utilising monthly data from January 1991 to June 2010. Indeed, an upward trend in financial convergence between ASEAN-5 and developing and developed countries has been noted.…”
Section: Us Stock Marketmentioning
confidence: 99%